Pengembangan Sistem Pemesanan Barang pada PT. AXC Tanah Tinggi Berbasis Android - Erasanti Meilani; Mira Ziveria (Research and Community Service INSTITUT TEKNOLOGI DAN BISNIS KALBIS, 2023)
The process of ordering goods at PT. AXC Tanah Tinggi still uses conventional method, which is coming directly to store, contacting by phone or Whatsapp. Customers have difficulty finding information on availability of goods. This study aims to build a system that provides information on availability of goods in real–time. System development method with System Development Life Cycle using prototyping model and Unified Modeling Language as a system model. The results of this study is an Android-based applications to manage the process of ordering goods. This application can be an intermediary between officers and customers in the process of ordering goods, so customers don’t need to come to company or contact officer. Based on the results of testing and evaluation, system can help customers to order goods and can be accessed by the officer quickly.